2004
DOI: 10.1093/ndt/gfh500
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of human polymorphonuclear neutrophils accelerated by dialysis membranes via the activation of the complement system

Abstract: Our results suggest that the acceleration of PMN apoptosis in the presence of CU is mediated via an antibody-dependent activation of the classical complement pathway mobilizing both caspase-dependent and -independent pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…We can only speculate whether this could be a consequence of a simple adsorption on the dialyzer surface or of an antigen-antibody reaction, such as the creation of HSP-anti-HSP complexes [28,29]. Indeed, such complexes are able to activate the complement, which is in accordance with the phenomenon observed in the course of a HD session [30,31]. The high anti-Hsp60 and anti-Hsp70 titers may also suppress Hsp60 concentrations, which was confirmed by the inverse correlation in our investigation and, probably, act in a detrimental manner.…”
Section: Discussionsupporting
confidence: 67%
“…We can only speculate whether this could be a consequence of a simple adsorption on the dialyzer surface or of an antigen-antibody reaction, such as the creation of HSP-anti-HSP complexes [28,29]. Indeed, such complexes are able to activate the complement, which is in accordance with the phenomenon observed in the course of a HD session [30,31]. The high anti-Hsp60 and anti-Hsp70 titers may also suppress Hsp60 concentrations, which was confirmed by the inverse correlation in our investigation and, probably, act in a detrimental manner.…”
Section: Discussionsupporting
confidence: 67%
“…For depletion of gamma globulin, serum aliquots were treated with an equal volume of protein G-coated Sepharose beads (GE Healthcare) as previously described (6). For total inhibition of the complement system, serum was heat inactivated for 30 min at 56°C as described previously (16,28). In order to inhibit the classical complement pathway, serum was treated with 10 Ϫ2 M EGTA and 10 Ϫ2 M MgCl 2 as previously described (5,8,28).…”
Section: Antibodiesmentioning
confidence: 99%
“…The dysfunctional state of inflammatory activation seen in dialysis patients could be caused by several different factors (Cheung et al 1989;Haag-Weber et al 1991;Descamps-Latscha 1993;Schindler et al 2001;Carracedo et al 2002;Horl 2002;Raj et al 2002;Kosch et al 2003;Koller et al 2004). Fragments of bacterial products can be present in small amounts in the dialysate and enter the circulation by diffusion through the dialysis membrane (Horl 2002).…”
Section: Patients On Hemodialysismentioning
confidence: 99%
“…This higher apoptotic activity in leukocytes is probably due to an antibodydependent activation of the complement system caused by the material or structure of the dialysis filters. It has been shown that heat-inactivation of complement components results in significantly lower apoptosis rates and that bioincompatible membranes cause a higher degree of apoptosis than biocompatible membranes (Koller et al 2004). The dialysis membrane permeability and flux are also of importance in determining the acute and chronic effects of hemodialysis on the inflammatory system.…”
Section: Patients On Hemodialysismentioning
confidence: 99%